Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. F. (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A.; François, L.; Ghislain, M.; Cheddadi, R. (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution

Climatic discrimination of Mediterranean broad-leaved sclerophyllous and deciduous forests in central Spain - Gavilán, Rosario; Fernández-González, Federico (Journal of Vegetation Science, 1997)
Abstract. Climatic differences between three types of deciduous (Quercus pyrenaica) and three types of sclerophyllous (Quercus rotundifolia) Mediterranean forests in the Spanish Sistema Central were analyzed by means of Canonical Discriminant Analysis and Jancey's Discriminant Analysis, applied in successive steps to data from 252 meteorological stations. Climatic data included temperature and precipitation records as well as bioclimatic indices. Discriminant analysis was applied to broad-leaved sclerophyllous and deciduous forest communities sampled at each meteorological station using phytosociological methods. Annual and seasonal (summer, spring) water availability are the most important factor controlling the distribution of the two physiognomic forest types; southwestern associations of Quercus pyrenaica and Q. rotundifolia differ from their colder homologues by annual and monthly temperatures; western associations were separated from eastern ones in terms of annual and seasonal precipitation gradients. Discriminant analysis was a good technique to explore climatic gradients not shown by other general ordination or classification methods.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Bioclimatic indices; climate; Continentality; Discriminant analysis; Summer aridity; Water availability